PROJECT-BASED ECONOMIC EDUCATION TO IMPROVE STUDENTS' CREATIVITY AND ENTREPRENEURSHIP - Amelia Khairina Ilmi; Supar Wasesa (JOURNAL OF EDUCATION SCIENCE, 2025)
This study aims to analyze the effectiveness of project-based economic education in enhancing students' creativity and entrepreneurship skills. The study employed a quantitative approach with a quasi-experimental pretest and posttest design involving eleventh-grade students in a senior high school in Indonesia. Data were collected through questionnaires, teacher observation sheets, and student project portfolios. The results indicated that project-based learning significantly improved students’ creativity, including their ability to generate new ideas, develop ideas, think critically, and solve problems innovatively. Students’ entrepreneurship skills also increased, reflected in business planning, resource management, market analysis, project implementation, and presentation of business outcomes. Project-based learning provided a more practical and meaningful learning experience while enhancing social skills such as collaboration, communication, and leadership. The study confirms that project-based economic education is effective in developing students’ creative and entrepreneurial competencies and can serve as a relevant learning strategy to meet real-world challenges.